Informal versus Formal: A Panel Data Analysis of Earnings Gaps in Madagascar - Christophe Jalil Nordman; Faly Rakotomanana; François Roubaud (Institute for the Study of Labor (IZA), 2016)
Little is known about the informal sector's income structure vis-à-vis the formal sector, despite its predominant economic weight in developing countries. While most of the papers on this topic are drawn from (emerging) Latin American, Asian or some African countries, Madagascar represents an interesting case. So far, very few studies in general, even less so in Sub-Saharan Africa, used panel data to provide evidence of the informal sector heterogeneity. Taking advantage of the 1-2-3 Surveys in Madagascar, a four-wave panel dataset (2000-2004), we assess the magnitude of various formal/informal sector earnings gaps. Is there an informal sector job earnings penalty? Do some informal sector jobs provide pecuniary premiums and which ones? Do possible gaps vary along the earnings distribution? Ignoring distributional issues is indeed a strong limitation, given the compound question of how informality affects earnings inequality. We address heterogeneity issues at three different levels: the worker, the employment status (wage employment vs. self-employment) and the earnings distribution. Standard earnings equations are estimated at the mean and at various conditional quantiles of the earnings distribution. The results suggest that the sign and magnitude of the formal-informal sector earnings gaps highly depend on the workers' employment status and on their relative position in the earnings distribution. In the case of a poor and fragile country like Madagascar, these findings provide new and robust empirical backups for the existence of a mix between the traditional exclusion vs. exit hypotheses of the informal sector.
Keywords: J21; J23; J24; J31; O17; 330; informal sector; earnings gap; transition matrix; panel data; Madagascar